Hadoop debug optimization - Siow, Llukelly Jian Yang. (2012)
This report described the design and development of a class which could aid in the debugging of Hadoop program. Common commercial used of Hadoop framework as mean for large data processing result in an increase of programming projects related to it. However, debugging of such program requires effort and time since it could only be done when the program is completed and not during the development phase. The developed class is capable of implementing with desired code and run. Tests were conducted to find the effects of the developed class when integrated to three chosen Hadoop program. Results found that run time of the program increased insignificantly and would not make any difference to user.